Effect of aging on the rate of muscle protein turnover in rat (Revista Española de Fisiología, 1996)
The urinary excretion of Nt-methylhistidine (e-methylhistidine, 3-MH, an index related to myofibrillar protein breakdown), as well as the rate of L-[14C]-tyrosine incorporation into gastrocnemius muscle (ks, fractional rate of muscle protein synthesis, evaluated by the constant infusion method) have been measured to assess the effect of aging on the rate of skeletal muscle protein turnover. In addition, nucleic acids, muscle protein and serum corticosterone levels were determined. Weaning rats were fed a 10% lactalbumin diet and killed in groups of seven when they were 35, 60, 120 and 300 days old. Apart from the rate of growth, no major differences were found between 35- and 60-day old animals. However, as compared to the youngest rats, 120-day old rats showed a significant reduction in the relative weight of the four muscles excised. Plasma corticosterone levels, increased as the animals became older. Finally, in the 300-day old rats, the reduced rate of growth was accompanied by a significant reduction in the relative organ weight (with the exception of soleus), 3-MH and Ks. It is concluded that aging caused a reduction in the rates of both protein breakdown and synthesis. The reduced muscle breakdown may not be due to a relative reduced muscle mass in elder rats since urinary 3-MH remained low even when expressed per creatinine output.